An Empirical Study on Talent Management Practices on Employee Satisfaction with reference to IT Industries, Hyderabad - V B DEEPTHI JYOTHI, Kiran Kumar Thoti, (European Economic Letters (EEL), 2023)
Organizational performance in the ever-changing IT sector is increasingly dependent on effective personnel management. This empirical research in Hyderabad, India's IT sector examines the connection between talent management techniques and worker happiness. Attracting, developing, and keeping top personnel has become an urgent issue for IT firms considering the industry's expansion and increased competition. This study used a mixed-methods design, conducting surveys and in-depth interviews with employees and HR experts from a wide range of IT companies in Hyderabad. Finding out how satisfied workers are with current talent management procedures is the primary goal of this research. This research shows that talent management techniques including hiring and training the right people, evaluating their progress, and rewarding their efforts have a major impact on IT workers' happiness. Leadership, work-life balance, and company culture also play significant roles in determining employee contentment. This study has double relevance. First, it provides helpful information for IT businesses in Hyderabad by outlining steps to take to improve talent management and hence, morale in the workplace. Second, it adds to the literature on talent management by demonstrating the practical effects of talent management on employee happiness in the IT sector. In conclusion, the importance of talent management strategies in fostering contentedness in Hyderabad's IT workforce is emphasized. A more competitive and sustainable IT sector in the area may be achieved by recognizing the importance of personnel management in boosting employee happiness.